Evaluation of biodegradability and environmental impact of biowaste leachate - Šabić Runjavec, Monika (Array, 2019)
As the world’s population and urbanization have significantly increased in the past few decades, the generation of municipal solid waste has accelerated on global scale. The biowaste disposal, which is an integral part of municipal waste, leads to leachate production. These kinds of wastewater are characterized by complex composition with very high concentrations of organic and inorganic pollution substances and toxicity, which may have harmful impact on the environment. This study investigated the physico-chemical and biological characterization of leachate from biowaste. The experiments were conducted in batch performance with initial concentration of leachate, expressed as chemical oxygen demand, 12.21 ± 0.46 g O2/L and pH value 4.05 ± 0.13. Obtained results showed that leachate from biowaste have high value of chemical oxygen demand, toxicity and low pH. Overall efficiency of the process of aerobic biodegradation was 89 %. The abundance of viable bacterial cells and development of activated sludge flocs during the experiment confirmed the biodegradability of leachate from biowaste.